New aspects of Krein's extension theory - Brasche, J. F.; Koshmanenko, V. D.; Neidhardt, H. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The extension problem for closed symmetric operators with a gap is studied. A new kind of parametrization of extensions (the so-called Krein model) is developed. The notion of a singular operator plays the key role in our approach. We give the explicit description of extensions and establish the spectral properties of extended operators.